(untitled) (American Journal of Islam and Society, 1985)
Muhammad Iqbal (1877-1938) was a man of great many ideas -sublime and serene, dynamic and romatic, provocative and profound. He was both a great poet and a serious thinker; but in poetic works lies enshrined most of his thought. It seems rather platitudinous to say, but it is important to note, that a poet is essentially a man of moods, and enjoys a sort of poetic license which is scrupulously denied to a prose-writer. Since a poet usually gives utterance to his reactions to a given situation, his utterances and ideas need not always be compatible with one another. Such was the case with Iqbal. During his poetic career, spanning some four decades, Iqbal had imbibed, approved, applauded and commended a great many ideas - ideas which occupied various positions along the spectrum on the philosophic, social, and political plane. Thus, at one time or another, he commended or denounced nationalism; propagated pan-Islamism and world Muslim unity; criticised the West for its materialism, for its cutthroat competition and for its values while applauding the East for its spiritualism and its concern for the soul; and condemned capitalism while preaching “a kind of vague socialism.”’ While, on the one hand, he steadfastly stood for “the freedom of ijtihad with a view to rebuild the law of Shari’at in the light of modern thought and experience,” and even attempted to reformulate the doctrines of Islam in the light of twentieth century requirements a la St. Augustine, he, on the other, also defended the orthodox position and the conservatism of Indian Islam on some counts. Though “inescapably entangled in the net of Sufi thought," he yet considered popular mysticism or “the kind of mysticism which blinked actualities, enervated the people and kept them steeped in all kinds of superstitions” as one of the primary causes of Muslim decline and downfall. It is to this aspect of Iqbal that Professor Hamilton A.R. Gibb was referring when he suggested: ...